2016
DOI: 10.1097/wnr.0000000000000551
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to the antinociceptive and hypothermic effects of morphine is mediated by multiple isoforms of c-Jun N-terminal kinase

Abstract: The abuse and overdose of opioid drugs are growing public health problems, globally. While progress has been made towards understanding the mechanisms governing tolerance to opioids, the exact cellular machinery involved remains unclear. However, there is growing evidence to suggest that c-Jun N-terminal Kinases (JNKs) play a major role in mu opioid receptor regulation and morphine tolerance. In this study, we aimed to determine the potential roles of different JNK isoforms in development of tolerance to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Quercetin, a PIK3cg inhibitor, previously has shown to reduce thermal hyperalgesia in diabetic mice (Anjaneyulu and Chopra, 2003). The thalidomide and SP600125 results presented here are supported by previous studies using rodent models of opioid tolerance (Babbini and Davis, 1972;Chai et al, 2011;Khan et al, 2017;Yuill et al, 2016). Thalidomide is also involved with the inhibition of TNF-α, a mediator of the inflammatory immune response (Klausner et al, 1996), which is important to note, as ligation of the spinal nerve creates a local inflammatory response contributing to the development of tolerance and/or mechanical hyperalgesia.…”
Section: Discussionsupporting
confidence: 85%
“…Quercetin, a PIK3cg inhibitor, previously has shown to reduce thermal hyperalgesia in diabetic mice (Anjaneyulu and Chopra, 2003). The thalidomide and SP600125 results presented here are supported by previous studies using rodent models of opioid tolerance (Babbini and Davis, 1972;Chai et al, 2011;Khan et al, 2017;Yuill et al, 2016). Thalidomide is also involved with the inhibition of TNF-α, a mediator of the inflammatory immune response (Klausner et al, 1996), which is important to note, as ligation of the spinal nerve creates a local inflammatory response contributing to the development of tolerance and/or mechanical hyperalgesia.…”
Section: Discussionsupporting
confidence: 85%
“…Since previous published work from our laboratory has demonstrated that JNK signaling is required for morphine tolerance, we examined whether JNK signaling was required for morphine-induced cross-tolerance to JWH-133. 29 , 30 This experiment was done by examining the efficacy of JWH-133 (1 mg/kg) anti-nociception in the formalin model using mice that received either five days of repeated morphine alone (10 mg/kg), mice that received daily pre-treatment with SP6 (3 mg/kg) prior to morphine (10 mg/kg), and mice receiving daily vehicle injections. Pre-treatment with SP6 was given 60 min before injection of morphine.…”
Section: Methodsmentioning
confidence: 99%
“…8 Previous studies showed that platelet-derived growth factor receptor β submit (PDGFRβ) could be phosphorylated during chronic morphine treatment. 9 Although PDGF-BB could activate microglia through PDGFRβ and produce tactile allodynia, 10 whether there is a link between activations of microglia and PDGFRβ in the mechanism of morphine tolerance is still unknown.…”
Section: Introductionmentioning
confidence: 99%